The Effect of Implementing the Problem Based Learning Model on Problem-Solving Skills in Geography Social Studies for 8th Grade Students at SMP Negeri 66, Central Maluku - Oca Aprilya Tualepe; Susan Evelin Manakane; Edward Gland Tetelepta (Jurnal Pendidikan Geografi Unpatti, 2024)
This research aims to determine the influence of the Problem Based Learning model on the ability to solve problems in the IPS Geography subject in class VIII SMP Negeri 66 Central Maluku. Because studying geography is not only being able to understand concepts, but also being able to apply these concepts in solving geographic problems. Solving Problems can be seen as a process, because in solving problems a series of concepts, rules and information that are known are used to solve the problem. Students are required to think systematically to solve geographic problems. Therefore, in teaching geography teachers should be able to create a learning atmosphere. , This type of research uses a quantitative approach to calculate the percentage of numbers from the results of the questionnaire regarding the influence of the problem based learning model on the ability to solve problems in geography subjects. So it can be concluded that there is a significant influence between problem based learning (variable x) on problem solving variables (y) Then, it can be seen from the calculation of the coefficient of determination that the problem based learning variable (x) influences problem solving (y) by 53.2% (R.Square in the Summary Model) while 46.8% is influenced by other variables which were not examined. in this research